Effect of the video output of the dental operating microscope on anxiety levels in a pediatric population during restorative procedures - Abrar Sayed; Vinisha Ranna; Dimple Padawe; Vilas Takate (Wolters Kluwer Medknow Publications, 2016)
Background: Adapting a child to the alien settings of a dental operatory is a major challenge to the dentist. Fear of the unknown and preconceived notions of dental pain causes anxiety in the pediatric patient. This often leads to disruptive and uncooperative behavior in the dental operatory. Many methods of behavior management have been described, of which the Tell-Show-Do (TSD) is an established and time-tested technique of behavior management. Aim: To determine if a live visual output of the dental operating microscope (DOM) could be used as an adjunct to the TSD technique, to involve the child more completely in the procedure and reduce the fear of the unknown. Materials and Methods: The study was a randomized, controlled, crossover, and cross-sectional clinical trial. Data were obtained from two visits. 90 children having carious lesions on both lower first molars, in the 7-9 years age group were selected and divided randomly into two groups. Restorative procedures were performed on one tooth per visit, with visits 1 week apart. Live display of the procedure was shown to the patient using video output of the DOM displayed on a 72 inch LCD monitor, angled for best visibility of the child. Anxiety levels were evaluated using Venhams picture selection test and pulse oximetry. Statistical Analysis: Student's t-test was used to compare the anxiety scores obtained from the two groups. Results: The results showed there was a decrease in the anxiety from the first visit to the second visit. (P = 0.05 for Group A and P = 0.003 for Group B). The patients preferred the visit in which the DOM was used. The operator reported an increased patient compliance and reduced patient movement in the visits in which the DOM was used. Conclusion: There is a reduction in anxiety from the first visit to the second visit for restorative treatment when the DOM is used.